Image charge screening: a new approach to enhance magnetic ordering temperatures - Altieri, Salvatore; Haverkort, Maurits W. (Arxiv, 2009)
We have tested the concept of image charge screening as a new approach to enhance magnetic ordering temperatures and superexchange interactions in ultra thin films. Using a 3 monolayer NiO(100) film grown on Ag(100) and an identically thin film on MgO(100) as model systems, we observed that the Neel temperature of the NiO film on the highly polarizable metal substrate is 390 K while that of the film on the poorly polarizable insulator substrate is below 40 K. This demonstrates that screening by highly polarizable media may point to a practical way towards designing strongly correlated oxide nanostructures with greatly improved magnetic properties.
Gesehen am 27.11.2017